2023
DOI: 10.1002/oto2.38
|View full text |Cite
|
Sign up to set email alerts
|

Cupulolithiasis: A Critical Reappraisal

Abstract: Objective To review the history and pathophysiologic theories for cupulolithiasis and canalith jam in benign paroxysmal positional vertigo. Data Sources PubMed, Google Scholar. Review Methods Three PubMed and Google Scholar searches were performed, keywords: “cupulolithiasis,” “apogeotropic [and] benign,” and “canalith jam,” resulting in 187 unique full‐text articles in English or with English translation. Figures—Labyrinthine photographs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Based on > 7 million SNPs compared between the two studies, the only locus that demonstrated significantly different alleles was on chromosome 19. While the Ice/Fin/UKB/US study had a strong hit suggesting ZNF91, our fine mapping analysis identified a credible set of SNPs within nearby LINC01224 [60]. LINC01224 affects the transcription of ZNF91 by regulation of long-range interactions between the ZNF91 enhancer and promoter [61].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on > 7 million SNPs compared between the two studies, the only locus that demonstrated significantly different alleles was on chromosome 19. While the Ice/Fin/UKB/US study had a strong hit suggesting ZNF91, our fine mapping analysis identified a credible set of SNPs within nearby LINC01224 [60]. LINC01224 affects the transcription of ZNF91 by regulation of long-range interactions between the ZNF91 enhancer and promoter [61].…”
Section: Discussionmentioning
confidence: 85%
“…To focus on the chronic cochleovestibular disorder of aging, we also excluded non-vestibular system gait disorders such as Parkinson's and other ataxias. We also eliminated over 25,000 of those diagnosed with traumatic brain injury (TBI), since TBI is a strong predictor of vertigo that is presumed to have a separate etiology [60]. We used the ICD diagnosis of "dizziness" in an attempt to capture the most common complaint of chronic imbalance in the elderly, even though that may include some disorders originating outside the vestibule.…”
Section: Discussionmentioning
confidence: 99%
“…Canalithiasis has been gradually accepted as the cause of most cases of BPPV (8), a process in which otoconia become detached from the otoconial membrane and fall into the semicircular canals before they can dissolve in the endolymph, hence transforming the affected canals into gravity-sensitive organs (9). Cupulolithiasis, in which freefloating endolymph debris adheres to the cupular membrane and renders the canal responsive to gravity (10) has been proposed to account for the remainder of BPPV cases, especially in older patients (10).…”
Section: Pathophysiology Of Bppvmentioning
confidence: 99%
“…Cupulolithiasis, in which freefloating endolymph debris adheres to the cupular membrane and renders the canal responsive to gravity (10) has been proposed to account for the remainder of BPPV cases, especially in older patients (10). Clinical signs of cupulolithiasis have been defined as apogeotropic nystagmus, with new maneuvers developed to manage either utricular-or canal-side cupulolithiasis; however, evidence that otoconia adhere strongly or persistently to the cupula is lacking (8).…”
Section: Pathophysiology Of Bppvmentioning
confidence: 99%
“…Cupulolithiasis is defined as the adherence of the otoconia debris or masses to the cupula which renders the gravity to be sensitive. However, there is no evidence that otoconia attach persistently or strongly to the cupula [18].…”
Section: • Pathophysiologymentioning
confidence: 99%